PEMANFAATAN BAKTERI ENTOMOPATOGENIK Bacillus cereus TERHADAP HAMA Spodoptera litura PADA TANAMAN KUBIS - Senewe, Emmy; Maramis, Redsway; Salaki, Christina L. (EUGENIA, 2012)
ABSTRACT This study aims to obtain entomopatogenik bacteria (Bacillus cereus) as a potential biological control of pests Spodoptera litura and determine the morphological characteristics and the potential power to kill isolate B. cereus. Explored endogenous bacteria from 99 soil samples from Minahasa regency, South Minahasa and Tomohon. Bacteria were isolated by selectively using methods Ohba and Aizawa identified by colony and cell morphology. The results showed that of the 99 soil samples obtained 141 isolates were identified as Bacillus cereus. Screening 141 isolates of the 80 isolates contained S.litura larvae that can cause deadly diseases and test larvae >50% after 96 hours with a dose of inoculum 1.5 x 107 spores / ml. Isolates that could potentially then be selected based on the pathogenicity then be developed into a biopesticide for pest control S. litura on cauliflower and broccoli plants. Keywords: Entomoopatogenic bacteria, Spodoptera litura, cabbage plants